‘Swachha Bharat Abhiyan’ (Clean India Campaign) : A Step Towards Social Accountability - Gore, Manasi; Dr. Meenal Annachhatre (European Journal of Multidisciplinary Studies, 2018)
India, one of the fastest growing economy in the World’s, faces the uncomfortable truth that many people still struggle with life on the poverty line. Despite high growth rates of GDP, millions of people in India still live with inadequate sanitation and health care facilities. This paradox of India clearly outlines the deprivation of certain strata of population leading to many social movements. A social movement is a sustained collective action over time for shared objectives and ideologies of a group to bring about changes in the existing social system. The health, sanitation and the welfare of masses is closely interlinked. It has been recognized that health is a key determinant of economic growth and better health leads to higher income which in turn leads to better health. Thus, health is a double edged sword if not addressed properly can work as a boomerang against the growth. For India it becomes indispensible to tackle the issue of health and cleanliness which is a fundamental component of human capital and the key to reap demographic dividend. Taking the holistic view of social accountability of the government towards the deprived social classes, the Indian government has offered various policy prescriptions towards cleanliness in terms of various schemes. This paper therefore intends to encompass such schemes with a special focus on ‘Swachha Bharat Abhiyan’, the most significant cleanliness campaign by the government of India. Various collective social movements in this regard were launched including that of Mahatma Gandhi, which triggered the effective public action and highlighted the role of participatory democracy in India.